Dynamics of Intra-Party Organisation in the Digital Age: A Grassroots Analysis of Digital Adoption. Issue 2 (17th May 2020) - Dommett, Katharine; Temple, Luke; Seyd, Patrick
Abstract: Over recent decades, scholars have explored political parties' adoption of digital technology. Tracing successive eras of change, scholarship has examined the degree to which digital disrupts or embeds traditional power structures—with many studies finding evidence of 'controlled-interactivity'. In this article, we revisit debates around the adoption of digital tools from a bottom-up perspective. Moving beyond attempts to categorise elite strategies for digital adoption, we consider practices on the ground to document how, in practice, digital technology is being taken up and used. Using a case study of the UK Labour Party, we categorise a range of different practices, highlighting and theorising the presence of digital adherents, laggards, entrepreneurs, renegades and refuseniks. Discussing the drivers of these practices, we offer new insight into variations in digital adoption and consider the significance of these trends for our understanding of party organisation.